1975
DOI: 10.1063/1.88432
|View full text |Cite
|
Sign up to set email alerts
|

New oscillation phenomena in VO2 crystals

Abstract: New oscillation phenomena in VO2 crystals were observed. The oscillation is generated in the temperature region of the crystal transition, and its voltage and frequency depend upon the ambient temperature. The waveform of the oscillation is a rectangular pulse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Similar oscillation phenomena in the systems consist of VO 2 and load resistors have also been reported in the 1970s. Taketa et al 16 observed an oscillation of 0.9 kHz in the circuit of a VO 2 bulk crystal and a load resistor at room temperature. Fisher 17 performed similar experiments on VO 2 needles, achieving an oscillation of 5.0 kHz.…”
Section: Introductionmentioning
confidence: 98%
“…Similar oscillation phenomena in the systems consist of VO 2 and load resistors have also been reported in the 1970s. Taketa et al 16 observed an oscillation of 0.9 kHz in the circuit of a VO 2 bulk crystal and a load resistor at room temperature. Fisher 17 performed similar experiments on VO 2 needles, achieving an oscillation of 5.0 kHz.…”
Section: Introductionmentioning
confidence: 98%
“…While these phenomena are attractive from the viewpoint of organic electronics, the oscillations have been achieved at as low as 4.2 K. The current oscillations in inorganic solids are achieved at both low temperature 12 and room temperature. [13][14][15][16] The realization of current oscillation at moderate temperature in organic materials is an important challenge.…”
mentioning
confidence: 99%
“…1 On the other hand, an electric-field-induced IM transition of VO 2 has also been reported several decades ago. 2 The current-voltage ͑I-V͒ characteristics of a VO 2 bulk sample possess a gradual change of the resistance, 3,4 while that of a VO 2 thin-film sample shows an extremely steep and discontinuous jump of resistance at the transition. [5][6][7] We note here that these I-V characteristics are symmetric about the origin, and therefore, this is a phenomenon different from that found in so-called resistance random access memory.…”
mentioning
confidence: 99%